Mathematics teachers' classroom assessment practices: a case study in a Maltese sixth form college - Buhagiar, Michael A. (2005)
This study explores the classroom assessment practices of twelve teachers teaching Pure Mathematics at Intermediate Level in a Maltese sixth form college. Apart from identifying the participants’ assessment views and practices (including how they explain their practices), the focus is on examining the implications that these views and practices have for leaning. In order to gain deeper insights into the underlying issues, the researcher - who is also a colleague of the participants - assumed the additional role of ‘thirteenth participant’. This duality proved particularly useful in understanding how the links between classroom assessment and learning can be strengthened.